Power characteristics analysis of a novel double-stator magnetic geared permanent magnet generator - Salihu, Mustafa Shehu; Misron, Norhisam; Othman, Mohammad Lutfi; Tsuyoshi, Hanamoto (MDPI, 2017)
This paper presents the design, fabrication and experimental power analysis of a novel double-stator magnetic geared permanent magnet (DSMGPM) machine which comprises of a double-stator permanent-magnet (PM) machine integrated a with triple rotor magnetic gear. The proposed machine can upscale the low-speed rotating magnetic field of the prime PMs on the prime rotor by using the modulation effect produced from the pole-pieces to high-speed rotating magnetic field from the field PMs. The low-speed prime rotor can also increase the speed of the field PM rotor and excite the coil windings to induce an electromotive force (EMF) resulting in electrical power. Thus, the machine is proposed for power generation in low-speed renewable energy applications such as wind turbines and tidal power generators. The proposed machine topology is presented and discussed while the performance power characteristics are evaluated experimentally. A prototype is fabricated and the measured results are in good agreement with the calculated results, therefore validating the proposed magnetic geared machine design.